Learning Sports Management with e-Learning - Redondo, Sara; Villalba, Ana María; Merino Jiménez, Álvaro (International Journal of Emerging Technologies in Learning (iJET), 2013)
Nowadays, hybridity is in demand from students in university degrees. They expect to be able to choose between on campus courses and online courses depending on their needs and wishes. Motivated by this, since academic year 2010-2011, the Universidad Europea de Madrid offers some of its traditional on campus undergraduate and graduate programs also in an on line format, under the concept of Universidad Personal. One of these programs, the MBA Masterâ??s Degree in Sports Management, was selected as the runner-up in the e-learning category of the 2012 International E-Learning Award (Academic Division), given by the International E-Learning Association. The purpose of this paper is to describe in more detail the objective and structure of this program, as well as the pedagogical and product model in which is based on, showing the different elements used for its design.